Construction Risk Management Using Organizational External Factors: A Brief Review - Nitin Verma (International Journal of Advanced Science and Technology, 2020)
The construction risks prevail in construction industry due to miscellaneous associated risks factor namely inefficient productivity by labor, scarcity of equipment, overrunning costs, delay in schedule of construction completion etc. The risk poses severe need for study of the problems and associated root causes amongst the interested research scholars, industry stake holders and construction planners and managers. The undertaken manuscript holds a brief of study through digital database available on World Wide Web for risk management. Additionally focus has also been delivered on tracing effects of external factors in viz. technological advancements, political factors, and economic considerations.